PROBLEM SOLVING IN THE ARMY IS THE BASIS SOLUTIONS TO SOFTWARE PROBLEMS MORAL AND PSYCHOLOGICAL TRAINING MILITARY SERVICE IN SCHOOLS - V.Yu. Znambetiv (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the moral and psychological training of youth for military service.